Nutrition, Lifestyle & Immunity: Maintaining Optimal Immune Function & Boost Our Immunity - Patil, Ankita P.; Patil, Tejaswini M.; Shinde, Asavari R; Vakhariya, Rohan R; Mohite, S. K; Magdum, C. S. (Asian Journal of Pharmaceutical Research and Development, 2021)
In the wake of the Covid-19 pandemic, people are increasingly becoming aware of the importance of good hygiene, healthy food for ensuring optimal immune function to keep viral/ other infections (communicable diseases) at bay. Immunity is the ability of body to resist a particular infection or toxin by the action of specific antibodies or sensitized white blood cells. The immune system is very complex. It is made up of several types of cells and proteins that have different jobs to do in fighting against foreign invaders. There are two types of immunity, innate immunity, acquired immunity. There are many different ways to boost immune system which include foods, medicines, nutraceuticals, vitamins, supplements, minerals, vaccine etc. Immunity is affected by different factors including age, gender, sleep cycle, stress, foods, exercise, genetic factors etc. Women have stronger immune response than men and hence they are more susceptible to autoimmune disorders like rheumatoid arthritis, IBD. Some environmental factors are also affecting the immunity. Person with weak immune system is more susceptible to various infections leads to various disorders.